2020
DOI: 10.3390/su13010245
|View full text |Cite
|
Sign up to set email alerts
|

Biological Characterization and Instrumental Analytical Comparison of Two Biorefining Pretreatments for Water Hyacinth (Eichhornia crassipes) Biomass Hydrolysis

Abstract: Water hyacinth is a rapidly growing troublesome aquatic weed plant, which causes eutrophication in water bodies and irreversible damage to the ecological system. In this work, we have investigated the water hyacinth biomass (WHB) hydrolysis efficacy of dilute alkaline (DA) pretreatment followed by biological pretreatment with white-rot fungus Alternaria alternata strain AKJK-2. The effectiveness of the dilute alkaline (DA) and biological pretreatment process on WHB was confirmed by using X-ray Diffraction (XRD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(9 citation statements)
references
References 54 publications
0
7
0
Order By: Relevance
“…These results are consistent with those of Liu et al [ 48 ], who used SEM and observed that the outer surface of treated corn cobs became cracked and somewhat wrinkled due to the breakage of the complex lignocellulosic structure of the biomass when treated by fungi. Singh et al [ 49 ] also found that microbial attack causes changes in the original fiber at the molecular level and determined that the formation of pores and cracks during degradation is correlated with the amount of reducing sugar produced.…”
Section: Resultsmentioning
confidence: 99%
“…These results are consistent with those of Liu et al [ 48 ], who used SEM and observed that the outer surface of treated corn cobs became cracked and somewhat wrinkled due to the breakage of the complex lignocellulosic structure of the biomass when treated by fungi. Singh et al [ 49 ] also found that microbial attack causes changes in the original fiber at the molecular level and determined that the formation of pores and cracks during degradation is correlated with the amount of reducing sugar produced.…”
Section: Resultsmentioning
confidence: 99%
“…These is proved by sugar production which was higher on the pre-treated samples compare to non-treated samples. Singh et al (2021) stated that the structure of lignocellulosic biomass through biological pretreatment showed pores and cracks caused by weakening of the cell walls during delignification, which increased yields of reducing sugars.…”
Section: Scanning Electron Microscopy (Sem) Analysismentioning
confidence: 99%
“…However, after biomass fractionation Figure 5(C) and (D), the samples showed cell deformation and fiber loosening suggestive to the effect of NADES. Through the micrographs obtained it is possible to observe the structural changes by the appearance of cracks, with probable appearance motivated by the dissolution of hemicelluloses and destructuring of the lignocellulosic material, changes such as increased surface area between the raw biomass (A) and the one treated with microwave radiation (D) (Singh et al, 2020).…”
Section: Scanning Electron Microscopymentioning
confidence: 99%